Learning Strategies at SD Muhammadiyah 1 Taman During the Covid-19 Pandemic - Egitayanti Aulia Rochman; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
The purpose of this research is to study and conclude the strategy of SD Muhammadiyah 1 Taman in implementing the teaching and learning process during the Covid 19 pandemic. This research method uses descriptive qualitative research methods. Descriptive qualitative methods describe social phenomena without hypotheses by analyzing the results to report detailed information obtained from information sources. Data collection techniques in this study were through in-depth interviews, documentation, and observation. Data collection techniques using triangulation techniques. Based on the research results, the strategy of SD Muhammadiyah 1 Taman in dealing with learning during the Covid 19 pandemic is to conduct online learning through digital multimedia by launching an application called "Mumtaz Smart". The "Mumtaz Smart" application is deliberately designed to be equipped with various facilities, such as: e-library, subject matter, virtual classroom, teleconference, video and learning media, student assignment notes, attendance data and student financial data. So that this strategic innovation is one way to support the learning process so that it continues to run well and effectively even though it cannot be face-to-face but still facilitates according to student needs.